A novel strain of Pseudozyma aphidis from mulberry parasitises the conidia of mulberry powdery mildew fungus Phyllactinia sp. and its biocontrol effect in the fields. Issue 1 (2nd January 2018) - Liu, Xiaoyuan; Qiu, Xin; Duan, Zhengqiao; Ping, Dongming; Zhou, Xineng; Yang, Jun; Zhou, Wei; Wan, Yongji
ABSTRACT: Plant surface is colonised with a vast community of non-pathogenic epiphytic microorganisms which play an important role in host defence. In the present study, we reported a fungus from mulberry leaf surface that showed an antagonistic effect against mulberry powdery mildew fungal pathogen Phyllactinia sp. This novel isolate is a yeast-like fungus that was identified as Pseudozyma aphidis CNm2012 based on morphologic and phylogenetic analysis. According to our research, P. aphidis CNm2012 directly acted on the powdery mildew conidia via parasitism which caused conidial atrophy, collapse and eventually, cleavage and death. During the parasitic process, we found the isolate could gather around the conidia of Phyllactinia sp. and form hyphae that grew on the conidial surface and utilise the conidia as a nutrient source. Field studies revealed that P. aphidis CNm2012 could suppress the disease incidence of mulberry powdery mildew caused by Phyllactinia sp., and reduce the disease severity. To our knowledge, it is the first report of P. aphidis directly against powdery mildew fungus Phyllactinia spp. by parasitism. Our results indicated that P. aphidis CNm2012 could be served as an environmentally friendly alternative of chemical pesticides to manage mulberry powdery mildew disease.